Comparative effects of vitamin b12, cobalt nitrate and ruminant stomach extract on the survival rate of indian carp during the first three weeks of life - Das, B C (Indian Journal of Fisheries, 2016)
Previous experiments in this laboratory have been concerned with waysto increase the survival of the Indian carp (Catla catla, Labeo rohita, Cirrhinamrigala) during the first three weeks of life following hatching. Enhancedsurvival, in comparison with untreated controls, was found for carptreated with vitamin B complex including B12 (Das and Krishnamurthy,1958 0).Â